Effect of Phylantus ninuri leaf extract on kidney and liver histopathological features in formaldehyde-exposed rats - Milla, Meidona Nurul; Istadi, Yani; Rizaldy, Rheza (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Formaldehyde (FA) metabolism in the body reduces glutathione levels, resulting in liver and kidney damage. Phylantus ninuri (meniran) has been demontrated to have hepatoprotective properties. However, the effect of meniran administration on the histological features of the liver and kidney in in formaldehyde-exposed rats has not been adequately studied. The study was aimed to determine the effect of meniran on the histopathological feature of liver and kidney cell. This was a posttest randomized control group design. A total of 24 male Wistar rats were divided into 4 groups of 6 rats each. Group 1 was a control group that received only oral formaldehyde. Group 2, Group 3, Group 4 was administered oral formaldehyde together with meniran extract at dose of 100 mg/kg BW, 200 mg/kg BW, and 300 mg /kg BW respectively for 14 days. The histopathological changes of the kidneys and liver were assesed using hematoxylin and eosin (HE) staining. The mean of kidney and liver damage in the meniran group at various doses was lower than that of control group. There was a significant difference in the mean of kidney damage between the control group and the meniran group at various doses (p<0.05). The mean histopathological score of liver damage showed a significant difference between the control group and various treatments (p<0.05). Ethanolic extract of meniran leaves ameliorates liver and kidney damage in formaldehyde-exposed rats.